PENGARUH CELEBRITY ENDORSER DAN IKLAN TERHADAP MINAT BELI SEPATU OLAHRAGA NIKE (STUDI KASUS PADA MAHASISWA STIE EKA PRASETYA) - Dedy - Lazuardi (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
This study aims to investigate the influence of celebrity endorsers and advertisements about the interest in buying Nike sports shoes. This is a case study of students of STIE Eka Prasetya-Medan and is a quantitative descriptive method. The population in this study was 623 students who had ever and never used Nike sports, while the sample was 86 students which was determined by using convenience sampling and Slovin formula. Multiple linear regression was used to analyze the data which showed that Y = 7.435a + 0.039X1 + 0.337X2 + 0.1e. The results of the study partially showed that the variable celebrity endorser partially proved to have an effect even not significant influence on the buying interest of Nike sport shoes. The evidence showed that from the value of t-count 0.289 smaller than t-table value 1.663 and the advertisement variable partially proved to have a positive and significant influence on buying interest of Nike sports shoes as evidenced by t-count 3,457 greater than the value of t table 1,663. Subsequently, the variations of celebrity endorsers and advertisements simultaneously have a positive effect on buying interest of Nike sports as evidenced by the f-count value of 13.762 greater than the f-table value of 2.37. Variable buying interest is influenced by celebrity endorser and advertising variables by 24.9%, while the remaining was 75.1% explained by the influence of factors or other outside variables such as price, quality, location, and others which were not discussed in this study.